Pengaruh Kompensasi dan Disiplin Kerja terhadap Loyalitas Guru di Sekolah Dasar Negeri di Kecamatan Samarinda Kota - Tasya Nur Safitri; Praja Hadi Saputra; Yulia Tri Kusumawati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to determine the effect of compensation and work discipline on teacher loyalty in the Samarinda City District. The research method used is quantitative, using observational and survey approaches. The sample comprised 93 respondents, consisting of teachers in the Samarinda City District. Data were collected via a questionnaire distributed through Google Forms using a Likert scale. The data were analyzed using SPSS for validity and reliability testing, classical assumption testing, multiple linear regression, t-test, and F-test as model fit tests (Goodness of Fit), as well as the coefficient of determination (Adjusted R²). The results indicate that both compensation and work discipline have a positive effect on teacher loyalty. Improvements in fair compensation provision and consistent enforcement of work discipline can enhance teachers’ loyalty to their employing institution. The model fit test (Goodness of Fit) shows that the regression model used in this study meets the criteria for adequacy and significance, making it suitable for predicting teacher loyalty.